Sex‐biased weaning and early childhood diet among middle holocene hunter–gatherers in Central California. Issue 4 (11th October 2013) - Eerkens, Jelmer W.; Bartelink, Eric J.
ABSTRACT This article evaluates age of weaning and early childhood diets of eight males and nine females from a Middle Holocene (4300–3000 BP) site in Central California, CA‐CCO‐548. All individuals died as adults. δ15N values from serial sections of dentin collagen in first molars suggest females were fully weaned, on average, by 3.6 years of age, about 0.4 years later than males in the sample, suggesting possible greater parental investment in female offspring. However, throughout childhood females consumed lower trophic‐level foods than males. This could indicate greater investment in males through provisioning of higher quality foods, or alternatively, some degree of independent foraging by males starting as early as 2 to 3 years of age. Even as adults, these same males and females consumed a different range of foods as indicated by their bone collagen δ13C and δ15N values. Overall, the data suggest children were enculturated early into their respective gendered diets, with girls consuming greater amounts of plant foods and boys consuming greater amounts of higher‐trophic level fish and meat protein. Am J Phys Anthropol 152:471–483, 2013. © 2013 Wiley Periodicals, Inc.